United Republic of Tanzania : Second Review Under the Policy Support Instrument; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report, 2008)
Fueled by a rebound in agriculture and improved electricity supply, economic growth reached 6.7 percent in 2006-07, and is on track to exceed 7 percent in 2007-08. In mid-2007, significant portfolio capital inflows put pressure on liquidity management. In the first quarter of 2007-08, fiscal performance was strong, but inflationary pressures intensified. After continuing to depreciate in most of 2007, the exchange rate recently reversed course. Strengthening monetary control is the key to reducing inflationary pressures and reining in high and volatile T-bill rates.